Determinants of Financial Management Behavior among Young Millennial Entrepreneurs - Ditya Permatasari; Nawirah Nawirah; Farahiyah Sartika (Jurnal Manajemen dan Kewirausahaan, 2024)
Effective financial management behavior can improve a person's financial well-being, while failure to manage personal finances can have long-term impacts. This research aims to examine the factors that influence Financial Management Behavior in young enterpreneurs. The research method used in this research is quantitative. The total number of respondents was 100 millennial entrepreneurs who are members of the Indonesian Young Entrepreneurs Association (HIPMI) in East Java Province spread across several cities. The sampling technique used was a purposive sampling technique with a data collection method in the form of a questionnaire. The research results show that Financial Literacy, Hedonism Lifestyle, Financial Attitude, and Self Control influence Financial Management Behavior while Income does not influence Financial Management Behavior. The novelty in this research is adding the influence of a lifestyle of hedonism and self-control in the context of millennial entrepreneurs, a group that is rarely the main focus in financial management studies in Indonesia. The results of this research provide practical implications for organizations such as HIPMI to develop financial education programs that not only increase financial literacy but also emphasize the importance of self-control and lifestyle management. In addition, this research can be a basis for the government to design policies that support the financial well-being of young entrepreneurs.